Barbie. The turquoise trail mystery - Balducci, Rita; Gitenstein, Judy Lew, Willie (Grolier Books New York, 1998)
While modeling in New Mexico, Barbie makes a new friend named Rosa. Soon they discover clues on a mysterious painting that lead them on a search through the desert that restores a great deal to Rosa and her family